Study on Optimal Regulation Model of Water Supply and Distribution Quantity in Irrigation Canal System Based on Cuckoo Optimization Algorithm - NONG Xizhi; LI Zhongan; JING Zheng; YE Ye (Renmin Zhujiang)
The main influencing factors of low water-use efficiency in irrigation multistage water supply systems are the leakage loss and the hydraulic loss of gate adjustment during water supply and distribution in the irrigation canal system. Optimal regulation of the water supply and distribution process in irrigation canals is a critical approach to achieving efficient water saving in agriculture. This paper took the three trunk canals of Zhanghe Irrigation District in Hubei Province as the research object, established an optimal water distribution model for irrigation canals under the comprehensive influence of the multistage canal system and multiple factors, and used the meta-heuristic optimization algorithm, namely Cuckoo search algorithm to solve the model. compared with the measured water distribution process, the irrigation duration of the optimized water distribution model and the conventional water distribution model was 13.2 d and 13.5 d, respectively, and the water distribution time was reduced by 45.00% and 43.75%. The process of water distribution flow was stable, which could effectively reduce the adjustment times of the gate. The leakage loss of the optimal water distribution model and conventional water distribution model obtained by the cuckoo algorithm (CS), particle swarm optimization (PSO), and differential evolution (DE) was reduced by 27.22%, 26.72%, and 27.06%, as well as 24.96%, 23.90%, and 24.55%, respectively. The CS could solve the water supply and distribution problem in a multi-dimensional irrigation canal system quickly, efficiently, and stably. This study provides a scientific reference for constructing and solving the optimal regulation model of water supply and distribution quantity in the irrigation canal system.